Pengaruh Akuntabilitas dan Indepedensi terhadap Kualitas Audit di Bank BJB Kantor Cabang Majalaya - Muhamad Syaepul; Jalaluddin Jalaluddin (Ma'soem University, 2022)
The background of this research is the fluctuation in the number of employees and the number of auditors that affect the number of audit case findings at Bank BJB Majalaya Branch Office. The purpose of this study was to determine the magnitude of the influence of accountability and independence both partially and simultaneously on audit quality at Bank BJB Majalaya Branch Office. This research is quantitative research with associative approach. The data used is primary data. By taking samples using the Slovin formula as many as 73 people from a large population of 88 people. The data collection techniques used were observation, interviews, literature study and questionnaires. The data processing analysis method in this study uses the application of Statistical Product and Service Solutions (SPSS) version 25 .The results showed that accountability affects the quality of audits at Bank BJB Majalaya Branch Office with the results of the t test where the t_hitung value is 2,862 > a t_tabel value of 1,993, there is an influence of indepedence on audit quality at Bank BJB Majalaya Branch Office, and simultaneously there is a simultaneous influence of accountability and indepedence on the quality of audits at Bank BJB Majalaya Branch Office where the results of the F test show that F_(calculate)> F_tabel or 179.984% > 3.13%.